The concept of sustainability in the social sciences (Sociology and social ecology in Croatia) - Lažnjak, Jasminka (2009)
Since 'Our common future' (1987) the term sustainable development became widely used concept in social sciences especially in social ecology and urban sociology. Why should social scientists deal with environment? The impact of society on the environment is the result of the development of modern technology which is in a great deal built in special institutional set up and it is socially constructed (Pinch, Bijker, Law 1989). The origin of our impact on the environment is socially marked and so are many consequences. In the paper are discussed different concepts of sustainability and their use in social sciences in the attempt to explain the main social processes of contemporary society. Concept of sustainable development of society and its social acceptance depends on trust, cooperation and values, basic elements of social capital. Another concept related to sustainability is risk defined in the theory of risk society by Ulrich Beck. How to implement principles of sustainable development in the network, risk and consumer society in crisis? The answers are stating point in various policy recommendations
Projekt MZOS
Projekt MZOS
ENG